FAKTOR-FAKTOR PENYEBAB ANAK JALANAN DI KOTA JAYAPURA, DISTRIK JAYAPURA SELATAN - Walopka, Yakobus; Ndoen, Marthen L.; Suwartiningsih, Sri (KRITIS, 2018)
The position of the Jayapura region is bordered by the State of Papua New Guinea and the Papua Strait, strategically as a route for alcohol and drug trade transactions, making it easier for street children to consume it. Unlike the phenomenon of street children in general, the typical characteristics of street children in Jayapura do not show differences in behavior with other children. Most street children are children aged <17 years. Therefore this study examines the factors that cause street children in the South Jayapura District, Jayapura City. This research uses descriptive qualitative method, with the Focus Group Discussion (FGD) data collection method in the community of street children. Based on the results of the analysis of the factors causing street children in Jayapura City, Jayapura District South, are environmental factors, economic factors and family factors. 1) Environmental factors, because the influence of peers at school and the influence of residence dominates its influence on the association of children who deliver them to be street children. 2) Family economic factors, street children who were originally looking for additional income for families by trading on the streets (hawkers, newspaper deliverymen), but along with the continuity of the routine process carried out on the streets, then they become accustomed to living as street children. 3) Family factors that dominate the cause of being street children because they do not get the attention and affection from their parents.